2017
DOI: 10.1016/j.jcmgh.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The Origins of Gastric Cancer From Gastric Stem Cells: Lessons From Mouse Models

Abstract: The cellular origin of digestive cancers has been a long-standing question in the cancer field. Mouse models have identified long-lived stem cells in most organ systems, including the luminal gastrointestinal tract, and numerous studies have pointed to tissue resident stem cells as the main cellular origin of cancer. During gastric carcinogenesis, chronic inflammation induces genetic and epigenetic alterations in long-lived stem cells, along with expansion of stem cell niches, eventually leading to invasive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 103 publications
(184 reference statements)
3
52
0
Order By: Relevance
“…Surface mucous epithelial cells in the gastric mucosa are columnar, and epithelial cells in the glands are cuboidal, but their morphological details and cellular makeup differ (16,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface mucous epithelial cells in the gastric mucosa are columnar, and epithelial cells in the glands are cuboidal, but their morphological details and cellular makeup differ (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells in the corpus express Sox2, Troy, Mist1, and eR1, whereas stem cells in the pyloric antrum express Sox2, Lgr5, CCK2R, eR1, Axin2, and Mist1 (18-25). Mouse model studies have shown that oncogenic events in gastric stem cells can frequently lead to carcinogenesis, although mutations targeted to chief cells also can cause these cells to dedifferentiate and acquire the potential to grow and regenerate gastric glands, sometimes forming metaplasia (17,21,22,(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer, primarily associated with Helicobacter pylori infectious inflammation, is one of the most common fatal cancers worldwide. 1,2 Aspirin exhibits a protective effect in gastrointestinal cancer, 3 including gastric cancer development, due to its antiinflammatory and antiplatelet functions, including induction of apoptosis 4 and inhibition of angiogenesis. 5 Previous meta-analyses have reported a potential relationship between aspirin use and prevention of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric cancer is a systemic disease, and its recurrence and metastasis are the major causes of poor prognosis (4). Similar to other solid tumors, the proliferation and metastasis of gastric cancer cells are regulated by multiple genes and multiple factors (22,23). miRNA has powerful post-transcriptional regulation function and a wide application prospect in tumor therapy.…”
Section: Discussionmentioning
confidence: 99%